Arthur And The Witch - Mercier,Johanne (London Phoenix Yard, 2013)
I'm Arthur and I'm seven, and the other day at Picket Lake, I found the best thing ever: a secret hord of blueberries! I picked millions of them as a surprise for Grandma. I ate quite a few of them too. If only I had known how angry this would make the Witch of Picket Lake. To make matters worse, Cousin Eugene had an idea..."
Keywords: English story book